Biological effects of plant residues with contrasting chemical compositions under humid tropical conditions: effects on soil fauna - Tian, G.; Brussaard, Lijbert; Kang, B. (Elsevier, 1993)
Effects of application of five types of plant residues [Acioa barteri, Gliricidia sepium and Leucaena leucocephala prunings, maize (Zea mays) stover and rice (Oryza sativa) straw] as mulch on soil fauna were examined under field conditions in the humid tropics in 1990 and 1991. Earthworm mean population over 2 years was higher under any type of plant residues by 41% compared to control. Leucaena prunings supported the highest earthworm population. Mulched plots also showed 177% higher mean termite population over 2 years than control. Highest termite population was observed in plots mulched with Acioa prunings followed by maize stover > rice straw >Leucaena prunings >Gliricidia prunings. The mean ant populations were 36% higher with Leucaena and Gliricidia prunings, and were not affected by Acioa prunings, maize stover and rice straw as compared to control. Millipede populations were not significantly affected by mulching. Earthworm populations were negatively correlated with the ratio of lignin : N of plant residues. Ant populations were significantly related to the N content of plant residues (R2 = 0.87 and 0.84 for 1990 and 1991 respectively). The results imply that chemical plant composition, particularly N and lignin contents, play a critical role in faunal abundance in the soil through their effect on palatability and decomposibility. Indirect microclimatic and mulching effects may also be important.